Visual Outcomes of Senile Cataract Patients Post-Cataract Surgery at JEC-Orbita Eye Clinic Makassar - Basalamah, Hadijah; Kusumawardhani, Sri Irmandha; Hidayat, Muh. Fadly; Anoez, Azizah; Namirah, Hannah Aulia (Journal La Medihealtico, 2024)
Cataracts are a major cause of blindness worldwide. World Health Organization (WHO) data in 2020, cataract is the most common eye disorder that causes blindness and visual impairment. Postoperative visual acuity is a simple direct parameter that can reflect the quality of cataract surgery and postoperative care. Descriptive in nature with a cross-sectional approach (cross-sectional) using secondary data obtained from medical records. The sampling technique used random sampling with a total of 97 samples. A study conducted at the JEC-ORBITA Main Eye Clinic in Makassar City from January 2024 to June 2024 on patients diagnosed with senile cataracts found 3466 patients. This study showed that the highest proportion occurred in female gender 54 (55.7%), elderly age category (60-74 years) 67 (69.1%), phacoemulsification surgery technique 97 (100%), unilaterally operated eyes on the left eye 35 (36.1%), nuclear cataract morphology 73 (75.3%), pre-operative vision dominated by moderate vision 62 (63.9%), post-operative vision on day 1 mild vision 51 (52.6%), day 7 mild vision 81 (83.5%) and day 30 it improved and increased in 86 (88.7%). Research result Visual Outcome Senile Cataract Patients Post Cataract Surgery at JEC-Orbita Makassar Main Eye Clinic from January 2024 to June 2024 showed improvement at the end of the fourth week of visits, by looking at the vision before and after cataract surgery.